Women's Power and Electability in Southeast Sulawesi: A Case Study for Provincial and National Legislative Candidate - Zuada, La Husen; Adriadi, Rekho; Kadir, Abdul (Jurnal Politik Indonesia: Indonesian Political Science Review, 2020)
This research examined the role of power in increasing the choice of women legislative candidates. Women's electability has increased in the four election periods (2004, 2009, 2014, 2019) in Southeast Sulawesi. The interesting thing on the results of the 2014 election found that eight of the nine elected women legislators are the wives of four active regents, three former regents, and the governor during the election process. They are the 'new face' in the politics and previously have never become a legislative member, except become the Chair of the Dharma Wanita who are accompanying their husbands as regional heads. The reasons for women's electability in the legislative underlie this research. Through a qualitative approach, this study found that the power resources were owned by their families (money and bureaucracy) and personal abilities were also the factors of choice. In the context of Southeast Sulawesi, this study found a change in the vote mobilization strategies. Ethnic mobilization (locality) that characterized the local politics of Southeast Sulawesi had a smaller impact on the election, whereas money politics (economic resource) and bureaucratic politicization (normative) had a strong impact on the voters. This study enriches the findings in the vote mobilization strategies, namely the combination of locality/friends-neighbors (ethnicity), money and bureaucracy as the factors of politicians' electability.